2017
DOI: 10.1111/coa.12938
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of the lymph node ratio as predictor of prognosis is higher in HPV‐negative than in HPV‐positive oropharyngeal squamous cell carcinoma

Abstract: Prognosis of primarily operated HPV-positive patients might be more dependent on the extent of primary tumour site, whereas prognosis of HPV-negative patients is based more on cervical metastatic spread, represented by LNR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The univariate analysis of the study by Meyer et al ( 40 ), which examined the prognostic influence of the lymph node ratio, also showed a significant influence of ENE on overall survival of HPV-positive patients with surgically treated OPSCC ( p = 0.012; ENE not included in the multivariate analysis) (surgery: n = 21, surgery + R(C)T: n = 67).…”
Section: Extranodal Extension In the Context Of The 8th Uicc Classifimentioning
confidence: 86%
See 1 more Smart Citation
“…The univariate analysis of the study by Meyer et al ( 40 ), which examined the prognostic influence of the lymph node ratio, also showed a significant influence of ENE on overall survival of HPV-positive patients with surgically treated OPSCC ( p = 0.012; ENE not included in the multivariate analysis) (surgery: n = 21, surgery + R(C)T: n = 67).…”
Section: Extranodal Extension In the Context Of The 8th Uicc Classifimentioning
confidence: 86%
“…The univariate analysis of the study by Meyer et al (40), which examined the prognostic influence of the lymph node ratio, also showed a significant influence of ENE on overall survival of HPV-positive patients with surgically treated OPSCC (p = 0.012; ENE not included in the multivariate analysis) (surgery: n = 21, surgery + R(C)T: n = 67). In 2017 Zhan et al published results of their validation of the new staging system based on 3,745 cases of HPV-positive OPSCC treated by surgery and neck dissection from the National Cancer Database (NCDB) for the years 2010-2014 (surgery only: n = 642, surgery + RT: n = 1,005, surgery + CRT: n = 1,773) (38).…”
Section: Extranodal Extension In the Context Of The 8th Uicc Classifimentioning
confidence: 87%
“…However, data regarding LNR in the setting of OPSCC and HPV are limited and controversial. Some studies suggest that LNR is a robust prognosticator for both HPV+ and HPV− OPSCC 25,26 while another suggest that LNR is only useful in HPV‐negative OPSCC 27 . Additionally, a well‐defined cutoff for LNR has yet to be well established in the setting of OPSCC when stratified for HPV status.…”
Section: Introductionmentioning
confidence: 99%
“…DISCUSSION An often cited strength of LNR is that it incorporates both surgical and sampling factors, thus giving insight into the quality of surgical dissection, the quality of histopathological analysis, and the extent of tumor growth patterns. 8,18,25,26 Previous studies assess LNR without controlling for potential inconsistencies from heterogeneity in surgical technique, anatomic subsite, and biological underpinning of disease (i.e., HPV-positive vs. HPVnegative disease). [25][26][27][28] Our study reports LNR in HPVrelated OPSCC and examines the validity of these findings in patients treated surgically with transoral robotic surgery.…”
Section: E187mentioning
confidence: 99%
“…8,18,25,26 Previous studies assess LNR without controlling for potential inconsistencies from heterogeneity in surgical technique, anatomic subsite, and biological underpinning of disease (i.e., HPV-positive vs. HPVnegative disease). [25][26][27][28] Our study reports LNR in HPVrelated OPSCC and examines the validity of these findings in patients treated surgically with transoral robotic surgery. Of note, LNR has been shown to be important in predicting disease-free and overall survival (OS) in squamous cell carcinoma from other head and neck subsites.…”
Section: E187mentioning
confidence: 99%